Solvent‐free Synthesis of Water‐Soluble New Pyridinium Amines: Spectroscopic Characterization, Biological Screening, and Interaction Study with DNA. Issue 7 (21st June 2017) - Zafar, Muhammad Naveed; Masood, Sara; Nazar, Muhammad Faizan; Raza, Muhammad Asam; Tahir, Muhammad Nawaz; Mugal, Ehsan Ullah; Rafique, Hummera; Gul‐e‐Saba,
Abstract : New water‐soluble pyridinium amines (2–8 ) were obtained by the solid‐state reactions of 4‐chloro‐1‐methylpyridin‐1‐ium triflate (1 ) and various primary aromatic amines. These compounds were characterized by 1 H, 13 C NMR, FTIR, UV–vis, and fluorescence spectroscopic methods along with single‐crystal X‐ray structure determination. The interaction potentials of all newly synthesized compounds with calf thymus DNA (CT‐DNA) were investigated by UV–vis and florescence spectroscopy accompanied by docking studies. UV–vis spectroscopy indicated that the binding of compounds with CT‐DNA takes place via the intercalative mode. The compounds were also screened for their potential as antioxidants and enzyme inhibition agents. Some compounds displayed excellent butyrylcholine and acetylcholine esterase inhibition activities and were effective in scavenging the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical in a dose‐dependent manner comparable to a standard. Abstract : New multi‐functional water soluble pyridinium amines as DNA intercalators, enzyme inhibitors and antioxidant agents